Confini, identit - Caliaro, Ilvano (Alpe Adria e dintorni, itinerari mediterranei, 2020)
The studies gathered in this volume analyze, in authors from Italy, Austria, Slovenia, Croatia, and neighboring territories, the complex relation between identity and borders, namely those between languages and cultures, that can cut through one single territory. We are looking at identities made of different layers and elements, blurred and oppressed, and constantly forced to redefine themselves, in dialog with one another.